Correlation of quality of life with executive function of brain in blind veterans - V. Nejati; R. Amini; A. Zabihzadeh (طب جانباز, 2012)
Background and Goal: Quality of life is a universal but abstract, mental and global concept that should be reduced to concrete, palpable and local part. The purpose of present study is evaluation of correlation of quality of life dimension with executive function of brain in blind veterans.